DETERMINANTS OF CONSUMPTION LEVEL OF POOR FAMILY IN SOUTH LEITIMUR DISTRICT, AMBON CITY - Derek Bakarbessy (Fakultas Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to analyze (1) the effect of income on the level of consumption, (2) the effect of the number of family members on the level of consumption, (3) the effect of the level of education on the level of consumption. The study was conducted in the South Leitimur District of Ambon City for 2 (two) months, from March to April 2022. The population used in this study were all the heads of poor families in the South Leitimur District of Ambon City as many as 1355 people. The sample is determined by simple random as much as 10% of the population as many as 135 people. The results of the study conclude that (1) there is a significant positive effect of income on the level of consumption, (2) there is a significant positive effect of the number of family members on the level of consumption, (3) there is a significant positive effect of the level of education on the level of consumption.